2018
DOI: 10.7717/peerj.5202
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and cobalt resistance properties of Sinorhizobium meliloti isolated from Medicago lupulina growing in gold mine tailing

Abstract: Sinorhizobium meliloti CCNWSX0020, isolated from root nodules of Medicago lupulina growing in gold mine tailings in the northwest of China, displayed multiple heavy metal resistance and growth promotion of M. lupulina. In our previous work, the expression level of dmeR and dmeF genes were induced by Cu2+ through comparative transcriptome approach. Based on protein analysis, the dmeF encoded for a protein which showed a 37% similarity to the cation transporter DmeF of Cupriavidus metallidurans, whereas dmeR enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Previous phenotypical characterizations of aitP-like genes in other rhizobial organisms point to a similar role of AitP in Co 2+ export and detoxification [17][18][19] and we have previously shown that AitP homolog in P. aeruginosa is involved in Fe 2+ homeostasis [7].…”
Section: Aitp Participates In Fe-homeostasissupporting
confidence: 52%
See 2 more Smart Citations
“…Previous phenotypical characterizations of aitP-like genes in other rhizobial organisms point to a similar role of AitP in Co 2+ export and detoxification [17][18][19] and we have previously shown that AitP homolog in P. aeruginosa is involved in Fe 2+ homeostasis [7].…”
Section: Aitp Participates In Fe-homeostasissupporting
confidence: 52%
“…Previous phenotypical characterizations of aitP -like genes in other rhizobial organisms point to a similar role of AitP in Co 2+ export and detoxification [17-19], and we have previously shown that the AitP homolog in P. aeruginosa is involved in Fe 2+ homeostasis [7]. However, a P-IB-type ATPase, nia , has been described as participating in Fe 2+ homeostasis in this organism [14], and the identification of an mbfA ortholog in Rm1021 genome led us to hypothesize that AitP in S. meliloti may play a non-classical role in Fe 2+ homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RcnR, and the homologous protein, DmeR, have also been functionally characterised in organisms which can synthesise B 12 de novo such as the human pathogen Salmonella , the leguminous plant symbionts Rhizobium leguminosarum and Sinorhizobium meliloti , and plant pathogen Agrobacterium tumefaciens [ [88] , [89] , [90] , [91] , [92] ]. In each case the genetic architecture differs from E. coli (which does not synthesise B 12 ) : in Salmonella , rcnB is not part of the rcnR operon, and in the plant microbes, DmeR regulates expression of dmeF , encoding a cation diffusion facilitator Ni(II)/Co(II)-efflux pump, distinct from RcnA [ 88 , 89 , 91 ]. The binding affinity, or stability of the Co(II)-RcnR complex as a K D , for Salmonella RcnR is 5 × 10 −10 M. Autoregulation by Salmonella RcnR confers hysteresis: This dampens the response to elevated cobalt and shifts the dynamic range away from what might be predicted from metal-affinity alone [ 93 ].…”
Section: The Components Of Cobalt Homeostasismentioning
confidence: 99%
“…DmeR is a Ni(II)-and Co(II)-responsive metalloregulator that has been identified in Rhizobium leguminosarum (R. leguminosarum), Agrobacterium tumefaciens (A. tumefaciens), Sinorhizobium meliloti [81][82][83]. The dmeRF operon encodes both DmeR and DmeF, a cation diffusion facilitator (CDF) [81].…”
Section: Dmermentioning
confidence: 99%